Investigating factors influencing the physicians’ adoption of electronic health record (EHR) in healthcare system of Bangladesh: An empirical study - Hossain, Akram (2019)
Electronic Health Record (EHR) can promote awareness or knowledge about healthcare among patients and healthcare professionals to improve collaboration between different governmental bodies, and enhance healthcare quality. The aim of the study is to identify the critical farctors affecting the physicians’ doption of EHR in healthcare system of Bangladesh by extending the Unified Theory of Acceptance and Use of Technology (UTAUT) to include Personal Innovativeness in Information Technology and Resistance to Change. A crosssectional survey questionnaire was used to collect data from 300 participants in different private and public hospitals in Dhaka, the capital city of Bangladesh. The study used partial least square (PLS) method, a statistical analysis technique based on the structural equation modeling (SEM), to analyze the collected data. The results of the study determined that Social Influence (β=0.19, P < 0.05), Facilitating Conditions (β=0.19, P < 0.05),and Personal Innovativeness in Information Technology (β=0.19, P < 0.05) had a significant influence on physicians’ Behavioral Intention to adopt the EHR system, whereas Performance Expectancy (β=0.08, P > 0.05), Effort Expectancy (β = -0.02, P > 0.05), and Resistance to Change (β=0.03, P > 0.05) had no significant influence. The findings suggest that policymakers should increase the adoption of the EHR system by developing social strategies to encourage physicians to stimulate each other to use the EHR system and ensuring technical sufficiency, training to facilitate the use of the EHR system. In addition, the policymakers should identify physicians who possess a propensity to experiment with new information technologies as well as reduce existing challenges and barriers such as computers crush, poor infrastructure with erratic power supply etc. Moreover, we identify future research areas that provide scholars opportunities to push theoretical and empirical boundaries and offer further insights into the study of the EHR system.